2014
DOI: 10.1007/s40263-014-0214-y
|View full text |Cite
|
Sign up to set email alerts
|

A Single-Dose Pilot Trial of Intranasal Rapid-Acting Insulin in Apolipoprotein E4 Carriers with Mild–Moderate Alzheimer’s Disease

Abstract: Larger clinical trials of longer duration are necessary to better understand the relationships between RA insulin, ApoE4 carrier status and cognitive performance in AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(77 citation statements)
references
References 16 publications
1
71
1
Order By: Relevance
“…Insulin was effective in improving performance on a verbal memory test in a group of AD and MCI patients; however, within these groups patients who were APOE ε 4 positive or female showed poorer recall following insulin administration compared to patients who did not possess this allele and males [17]. Similar results were found with rapid-acting insulin, which is thought to have superior effects intranasally when compared to regular insulin, in APOE ε4 positive AD patients [18]. …”
Section: Introductionmentioning
confidence: 79%
“…Insulin was effective in improving performance on a verbal memory test in a group of AD and MCI patients; however, within these groups patients who were APOE ε 4 positive or female showed poorer recall following insulin administration compared to patients who did not possess this allele and males [17]. Similar results were found with rapid-acting insulin, which is thought to have superior effects intranasally when compared to regular insulin, in APOE ε4 positive AD patients [18]. …”
Section: Introductionmentioning
confidence: 79%
“…Other studies have examined the effect of intranasal insulin on memory, particularly in cognitively impaired subjects, and the results have been mixed. For instance, intranasal insulin improved memory performance in some studies (Craft et al, 2012; Reger et al, 2008b) while other studies found insulin’s effects on memory are dependent on ApoE genotype with reports of beneficial effects (Reger et al, 2006; Reger et al, 2008a), no effect (Rosenbloom et al, 2014), or a negative effect (Claxton et al, 2015) in APOE ε4 noncarriers. Another study found effects only when sex and ApoE genotype were considered.…”
Section: Discussionmentioning
confidence: 96%
“…However, not all studies show a beneficial effect of insulin in AD; for instance, Apolipoprotein E (APOE) ε4 carriers generally do not exhibit improved cognition (Rosenbloom et al, 2014). Furthermore, our group has shown that the relationship between circulating insulin, cognition, and brain structure differs between individuals with normal cognition and AD (Burns et al, 2007; Burns et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, high dose of insulin experienced increased peripheral insulin resistance in APOE negative patients (Claxton et al, 2015). These findings suggest that groups with different genetic risks for AD may show differential dose-response curves following intranasal insulin administration (Reger et al, 2008a; Rosenbloom et al, 2014). Further, it is reported that insulin treated subjects retained more verbal information, improved attention and raised fasting plasma Aβ 40 /Aβ 42 ratio (Reger et al, 2008b).…”
Section: Intranasal Insulin Improves Memory In the Healthy Humans As mentioning
confidence: 99%